Anti-UV screen protection film and preparation method thereof

By introducing modified zinc sulfide and a titanium dioxide reflective film layer with raised dots in the screen protector, the UV resistance is improved, the problem of insufficient UV resistance in the prior art is solved, and higher reflectivity and lower The transmittance rate extends the service life of the screen.

CN119119883APending Publication Date: 2024-12-13TAIHU JINZHANG TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411168051.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-23
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

When facing ultraviolet rays, the existing screen protectors have difficulty in breaking through their UV resistance, high transmittance and low reflectivity, making it difficult to effectively extend the service life of the screen.

Method used

The anti-UV screen protector adopts a multi-layer structure, including a release film layer, a pressure-sensitive adhesive layer, a tempered glass film layer, a titanium dioxide reflective film layer and a UV absorbing film layer. By introducing modified zinc sulfide into the titanium dioxide reflective film layer and Set evenly distributed bumps to improve reflectivity and dispersion, and increase the length of the light propagation path.

Benefits of technology

It significantly improves the UV resistance of the screen protector, reduces the UV transmittance, improves the reflectance, and extends the service life of the screen.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses an anti-UV screen protection film and a preparation method thereof, and relates to the technical field of protection films, and the anti-UV screen protection film comprises a release film layer, a pressure-sensitive adhesive layer, a tempered glass film layer, a titanium dioxide reflective film layer, a UV absorption film layer and a PET synthetic film layer which are stacked in sequence; wherein the titanium dioxide reflecting film layer comprises modified zinc sulfide, and the modified zinc sulfide comprises zinc sulfide nanoparticles and an S-P-N type additive in a mass ratio of 1: (0.5-0.8); the preparation method of the modified zinc sulfide comprises the following steps: mixing zinc sulfide nanoparticles with an S-P-N type additive, and then carrying out ultrasonic stirring, so that the zinc sulfide nanoparticles are fully and uniformly mixed in the S-P-N type additive, thereby obtaining the modified zinc sulfide, the modified zinc sulfide is introduced on the titanium dioxide reflecting film layer, and the uniformly distributed salient points are arranged on the titanium dioxide reflecting film layer, so that the reflectivity of the titanium dioxide reflecting film layer to UV is improved, and the anti-UV performance of the protective film is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of protective films, and in particular to an anti-UV screen protective film and a preparation method thereof. Background Art

[0002] Ultraviolet (UV) light is a type of high-energy radiation in sunlight. Long-term exposure to it can damage the screen protector material, accelerate screen aging, and reduce the screen's service life.

[0003] The impact of ultraviolet rays is particularly significant for screens that are often used outdoors, such as outdoor advertising display screen protective films, outdoor surveillance camera protective films, and electronic device screen protective films that are temporarily used outdoors, such as mobile phone protective films and tablet computer protective films.

[0004] In order to extend the service life of the screen, improve the display effect, and reduce the damage of ultraviolet rays to the screen material, it is necessary to develop a screen protective film with anti-UV function. In the prior art, the screen protective film is often designed as a multi-layer structure, and a UV absorption layer is designed on the outer layer of the functional layer to resist the damage caused by UV to the functional layer. However, the transmittance of UV to the better screen protective film in the prior art can usually be maintained at 2-3%, and the reflectivity can be maintained at 95-99%. Although such a screen protective film can achieve better anti-UV performance, it is difficult to achieve a higher breakthrough.

[0005] Based on this, the present invention is committed to realizing a screen protective film with better anti-UV effect on the basis of the prior art. Summary of the invention

[0006] The purpose of the present invention is to provide an anti-UV screen protection film and a preparation method thereof; to solve the following technical problems:

[0007] How to improve the UV resistance of screen protectors?

[0008] The purpose of the present invention can be achieved through the following technical solutions:

[0009] In a first aspect, the present invention discloses an anti-UV screen protective film, comprising a release film layer, a pressure-sensitive adhesive layer, a tempered glass film layer, a titanium dioxide reflective film layer, a UV absorption film layer and a PET synthetic film layer stacked in sequence; wherein the titanium dioxide reflective film layer comprises modified zinc sulfide, and the components of the modified zinc sulfide include zinc sulfide nanoparticles and SPN type additives in a mass ratio of 1: (0.5-0.8).

[0010] Preferably, the mass ratio of zinc sulfide nanoparticles to the SPN type additive is 1:0.65.

[0011] Preferably, the release film layer is a silicone release film or a fluorine release film.

[0012] Preferably, the pressure-sensitive adhesive layer is a silicone pressure-sensitive adhesive or a polyurethane pressure-sensitive adhesive.

[0013] In a further embodiment of the present invention: the thickness of the release film layer is 50-80 um, the thickness of the pressure-sensitive adhesive layer is 10-30 um, the thickness of the tempered glass film layer is 60-100 um, the thickness of the titanium dioxide reflective film layer is 20-50 um, the thickness of the UV absorbing film layer is 20-50 um, and the thickness of the PET synthetic film layer is 30-70 um;

[0014] Preferably, the thickness of the release film layer is 60-70um, the thickness of the pressure-sensitive adhesive layer is 15-25um, the thickness of the tempered glass film layer is 70-90um, the thickness of the titanium dioxide reflective film layer is 30-40um, the thickness of the UV absorption film layer is 30-40um, and the thickness of the PET synthetic film layer is 40-60um;

[0015] More preferably, the thickness of the release film layer is 65um, the thickness of the pressure-sensitive adhesive layer is 20um, the thickness of the tempered glass film layer is 80um, the thickness of the titanium dioxide reflective film layer is 35um, the thickness of the UV absorption film layer is 35um, and the thickness of the PET synthetic film layer is 50um.

[0016] In a further embodiment of the present invention, the modified zinc sulfide is prepared by mixing zinc sulfide nanoparticles with an SPN type additive and then performing ultrasonic stirring to fully and evenly mix the zinc sulfide nanoparticles with the SPN type additive to obtain modified zinc sulfide.

[0017] Preferably, the SPN type additive is a nano-boronated rare earth super-heavy load vehicle gear oil compound (T4408B).

[0018] Zinc sulfide nanoparticles have the highest reflectivity among all materials, and their reflectivity can reach 2.37. They also have good optical and electrical properties, and their crystal structure can be controlled. Due to the quantum effect of zinc sulfide nanoparticles, their surface energy is high, but they are prone to aggregation, so their dispersion performance is poor. Based on this, by mixing SPN type additives with zinc sulfide nanoparticles, on the one hand, the SPN type additives will be wrapped on the surface of zinc sulfide nanoparticles, changing their surface properties and avoiding the phenomenon of easy aggregation, which is beneficial to improving the dispersibility of zinc sulfide nanoparticles. On the other hand, the sulfur element in the SPN type additive can exist in the polymer in the form of thioester bonds, thioether bonds, thiocarbamates and sulfone groups, thereby effectively improving the reflectivity of the material.

[0019] In a further embodiment of the present invention, the method for preparing the titanium dioxide reflective film layer comprises the following steps:

[0020] S1: At room temperature, slowly drop titanium alkoxide into the solvent while stirring, then slowly add an appropriate amount of hydrochloric acid while stirring, adjust the pH to 1-2, and react for 2-3 hours to obtain a uniform and transparent sol solution;

[0021] Preferably, the mass ratio of the titanium alkoxide to the solvent is 1:(2-5), more preferably 1:3.

[0022] Preferably, the titanium alkoxide is tetrabutyl titanate or tetraisopropoxy titanium, more preferably tetrabutyl titanate;

[0023] Preferably, the solvent is isopropanol, propanol or ethanol, more preferably ethanol.

[0024] S2: uniformly mixing the sol solution with the modified zinc sulfide in a mass ratio of 2:(0.5-1.2) to obtain a mixed sol solution;

[0025] Preferably, the mass ratio of the sol solution to the modified zinc sulfide is 2:(0.6-1), more preferably 2:0.8.

[0026] S3: evenly coating the mixed adhesive on the cleaned substrate material, and then vacuum drying the substrate material coated with the mixed adhesive at 60-80° C. for 7-8 hours to completely evaporate the solvent to obtain a film;

[0027] Preferably, the substrate material is a glass plate or a silicon plate, preferably a glass plate.

[0028] Preferably, the base material coated with the mixed glue is vacuum dried in a vacuum drying oven.

[0029] S4: placing the substrate material loaded with the thin film in a heating furnace for heat treatment at 400-600° C. for 2-4 hours, so that the organic matter in the thin film is completely decomposed to obtain a titanium dioxide thin film;

[0030] Preferably, the heating furnace is a muffle furnace.

[0031] S5: After the titanium dioxide film is taken out of the heating furnace, a hot pressing plate with pits evenly distributed on the hot pressing surface is immediately used to hot press one side of the film. After cooling to room temperature, the film is peeled off from the base material to obtain a titanium dioxide reflective film layer with bumps distributed on the surface.

[0032] Preferably, the shape of the pit is hemispherical, the diameter is 10-20um, the depth is 5-10um, and the distance between the center points of two adjacent pits is 40-60um;

[0033] More preferably, the shape of the pit is hemispherical, with a diameter of 15 um, a depth of 8 um, and a distance between the center points of two adjacent pits is 50 um.

[0034] By providing evenly distributed convex dots on the titanium dioxide reflective film layer and strictly controlling the size and distribution density of the convex dots (if the convex dots are distributed too densely, it may cause multiple reflections and scattering of light inside the material, thereby reducing the transmittance and reflectivity of the light; if the convex dots are distributed too dispersedly, the reflection of light inside the material is too little, and it is difficult to achieve the best reflection effect), the presence of the convex dots can change the propagation path of light on the surface of the material, causing the light to be reflected and scattered when it is incident on the convex dots; this reflection and scattering phenomenon can increase the propagation path length of light inside the material, thereby improving the reflectivity.

[0035] In a second aspect, the present invention further discloses a method for preparing the anti-UV screen protective film as described above, comprising the following steps:

[0036] Step 1: first, evenly apply the tempered glass glue on the side of the titanium dioxide reflective film layer without convex points, and form a tempered glass film layer after drying, and then evenly apply the UV absorbing glue on the side of the titanium dioxide reflective film layer with convex points, and form a UV absorbing film layer after drying;

[0037] Step 2: Evenly coat the surface of the tempered glass film layer with a pressure-sensitive adhesive layer, and then attach a release film layer to the pressure-sensitive adhesive layer;

[0038] Step 3: Evenly coat the UV absorbing film layer with PET synthetic glue to form a PET synthetic film layer after drying, thereby obtaining a UV screen protective film.

[0039] Beneficial effects of the present invention:

[0040] (1) The present invention improves the reflectivity of the titanium dioxide reflective film layer to UV by introducing modified zinc sulfide on the titanium dioxide reflective film layer, thereby improving its anti-UV performance; the zinc sulfide nanoparticles in the modified zinc sulfide have the highest reflectivity among all materials, and its reflectivity can reach 2.37, and it also has good optical and electrical properties, and its crystal structure can be controlled. Due to the quantum effect of the zinc sulfide nanoparticles, its surface energy is high, but it is easy to aggregate, so its dispersion performance is poor. Based on this, by mixing the SPN type additive with the zinc sulfide nanoparticles, on the one hand, the SPN type additive will be wrapped on the surface of the zinc sulfide nanoparticles, change its surface properties, avoid the phenomenon that it is easy to aggregate, and is beneficial to improve the dispersibility of the zinc sulfide nanoparticles. On the other hand, the sulfur element in the SPN type additive can exist in the polymer in the form of thioester bonds, thioether bonds, thiocarbamates and sulfone groups, thereby effectively improving the reflectivity of the material. Titanium dioxide itself has good reflectivity, so the introduction of modified zinc sulfide can further improve its reflectivity.

[0041] (2) The present invention improves the anti-UV performance of the screen protective film by providing evenly distributed protrusions on the titanium dioxide reflective film layer and strictly controlling the size and distribution density of the protrusions. The presence of the protrusions can change the propagation path of light on the surface of the material, causing the light to be reflected and scattered when it is incident on the protrusions; this reflection and scattering phenomenon can increase the propagation path length of the light inside the material, thereby improving the reflectivity and further improving its anti-UV performance; when UV is irradiated onto the screen protective film of the present invention, it first passes through the PET synthetic film layer and enters the surface of the UV absorbing film layer, most of the UV light is absorbed by the UV absorbing film layer, and a small part of the UV light passes through the UV absorbing film layer and enters the titanium dioxide reflective film layer, and cannot enter the tempered glass film layer after being reflected by the film, thereby improving the anti-UV performance of the screen protective film. DETAILED DESCRIPTION

[0042] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.

[0043] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.

[0044] Example 1

[0045] Preparation of modified zinc sulfide:

[0046] 100 g of zinc sulfide nanoparticles and 50 g of T4408B were added into an ultrasonic mixer and stirred at a frequency of 25 kHz for 30 min to obtain modified zinc sulfide.

[0047] Example 2

[0048] Preparation of modified zinc sulfide:

[0049] 100 g of zinc sulfide nanoparticles and 65 g of T4408B were added into an ultrasonic mixer and stirred at a frequency of 25 kHz for 30 min to obtain modified zinc sulfide.

[0050] Example 3

[0051] Preparation of modified zinc sulfide:

[0052] 100 g of zinc sulfide nanoparticles and 80 g of T4408B were added into an ultrasonic mixer and stirred at a frequency of 25 kHz for 30 min to obtain modified zinc sulfide.

[0053] Example 4

[0054] Prepare the hot press plate:

[0055] Take an austenitic stainless steel plate with a length of 10 cm, a width of 5 cm and a thickness of 4 mm. Use a laser beam to evenly open hemispherical pits on one side of the stainless steel plate. The diameter of the pits is 10 um, the depth is 5 um, and the distance between two adjacent pits is 40 um.

[0056] Example 5

[0057] Prepare the hot press plate:

[0058] Take an austenitic stainless steel plate with a length of 10 cm, a width of 5 cm and a thickness of 4 mm. Use a laser beam to evenly open hemispherical pits on one side of the stainless steel plate. The diameter of the pits is 15 um, the depth is 8 um, and the distance between two adjacent pits is 50 um.

[0059] Example 6

[0060] Prepare the hot press plate:

[0061] Take an austenitic stainless steel plate with a length of 10 cm, a width of 5 cm and a thickness of 4 mm. Use a laser beam to evenly open hemispherical pits on one side of the stainless steel plate. The diameter of the pits is 20 um, the depth is 10 um, and the distance between two adjacent pits is 60 um.

[0062] Example 7

[0063] Preparation of titanium dioxide reflective film layer:

[0064] At room temperature, 30 g of ethanol was injected into the stirring tank, and then 10 g of tetrabutyl titanate was slowly added to the ethanol while stirring, and then hydrochloric acid was slowly added under stirring to adjust the pH to 1.5. After reacting for 2.5 h under stirring, a uniform and transparent sol solution was obtained. 10 g of the modified zinc sulfide prepared in Example 1 was added to the sol solution, and stirring was continued for 20 min to obtain a mixed sol solution. The mixed sol solution was evenly coated on a cleaned glass plate, and then the substrate material coated with the mixed sol solution was placed in a vacuum drying oven. The titanium dioxide film was taken out of the heating furnace and immediately hot-pressed on one side of the film using the hot pressing plate prepared in Example 4. After cooling to room temperature, the film was peeled off from the glass plate using a blade to obtain a titanium dioxide reflective film layer with bumps distributed on the surface. The thickness of the film was 31 um.

[0065] Example 8

[0066] Preparation of titanium dioxide reflective film layer:

[0067] At room temperature, 30 g of ethanol was injected into a stirring tank, and then 10 g of tetrabutyl titanate was slowly added dropwise to the ethanol while stirring. Subsequently, hydrochloric acid was slowly added dropwise under stirring to adjust the pH to 1.5. After reacting for 2.5 h under stirring, a uniform and transparent sol solution was obtained. 12 g of the modified zinc sulfide prepared in Example 2 was added to the sol solution, and stirring was continued for 20 min to obtain a mixed sol solution. The mixed sol solution was evenly coated on a cleaned glass plate, and then the substrate material coated with the mixed sol solution was placed in a vacuum drying oven. The film was dried at 65°C for 7.8 hours to completely evaporate the ethanol and obtain a film. The glass plate loaded with the film was placed in a muffle furnace and heated at 450°C for 3.5 hours to completely decompose the organic matter in the film and obtain a titanium dioxide film. After the titanium dioxide film was taken out of the heating furnace, the hot pressing plate prepared in Example 5 was immediately used to perform hot pressing on one side of the film. After cooling to room temperature, the film was peeled off from the glass plate with a blade to obtain a titanium dioxide reflective film layer with bumps distributed on the surface. The thickness was measured to be 36 um.

[0068] Example 9

[0069] Preparation of titanium dioxide reflective film layer:

[0070] At room temperature, 30 g of ethanol was injected into the stirring tank, and then 10 g of tetrabutyl titanate was slowly added to the ethanol while stirring, and then hydrochloric acid was slowly added under stirring to adjust the pH to 1.5. After reacting for 2.5 h under stirring, a uniform and transparent sol solution was obtained. 16 g of the modified zinc sulfide prepared in Example 2 was added to the sol solution, and stirring was continued for 20 min to obtain a mixed sol solution. The mixed sol solution was evenly coated on a cleaned glass plate, and then the substrate material coated with the mixed sol solution was placed in a vacuum drying oven. , dried at 70°C for 7.5h to completely volatilize the ethanol and obtain a thin film; placing the glass plate loaded with the thin film in a muffle furnace and heating it at 500°C for 3h to completely decompose the organic matter in the film to obtain a titanium dioxide thin film; after taking the titanium dioxide thin film out of the heating furnace, immediately use the hot pressing plate prepared in Example 5 to hot press one side of the film, and after cooling to room temperature, use a blade to peel the film from the glass plate to obtain a titanium dioxide reflective film layer with bumps distributed on the surface. The thickness of the film is measured to be 35um.

[0071] Example 10

[0072] Preparation of titanium dioxide reflective film layer:

[0073] At room temperature, 30 g of ethanol was injected into a stirring tank, and then 10 g of tetrabutyl titanate was slowly added dropwise to the ethanol while stirring. Subsequently, hydrochloric acid was slowly added dropwise under stirring to adjust the pH to 1.5. After reacting for 2.5 h under stirring, a uniform and transparent sol solution was obtained. 20 g of the modified zinc sulfide prepared in Example 2 was added to the sol solution, and stirring was continued for 20 min to obtain a mixed sol solution. The mixed sol solution was evenly coated on a cleaned glass plate, and then the substrate material coated with the mixed sol solution was placed in a vacuum drying oven. The film was dried at 75°C for 7.2 hours to completely evaporate the ethanol and obtain a thin film. The glass plate loaded with the thin film was placed in a muffle furnace and heated at 550°C for 2.5 hours to completely decompose the organic matter in the film and obtain a titanium dioxide thin film. After the titanium dioxide thin film was taken out of the heating furnace, the hot pressing plate prepared in Example 5 was immediately used to perform hot pressing on one side of the film. After cooling to room temperature, the film was peeled off from the glass plate with a blade to obtain a titanium dioxide reflective film layer with bumps distributed on the surface. The thickness was measured to be 39 um.

[0074] Embodiment 11

[0075] Preparation of titanium dioxide reflective film layer:

[0076] At room temperature, 30 g of ethanol was injected into the stirring tank, and then 10 g of tetrabutyl titanate was slowly added to the ethanol while stirring, and then hydrochloric acid was slowly added under stirring to adjust the pH to 1.5. After reacting for 2.5 h under stirring, a uniform and transparent sol solution was obtained. 24 g of the modified zinc sulfide prepared in Example 3 was added to the sol solution, and stirring was continued for 20 min to obtain a mixed sol solution. The mixed sol solution was evenly coated on a cleaned glass plate, and then the substrate material coated with the mixed sol solution was placed in a vacuum drying oven. The titanium dioxide film was taken out of the heating furnace and immediately hot-pressed on one side of the film using the hot pressing plate prepared in Example 5. After the film was cooled to room temperature, the film was peeled off from the glass plate using a blade to obtain a titanium dioxide reflective film layer with bumps distributed on the surface. The thickness of the film was measured to be 39 um.

[0077] Comparative Example 1

[0078] Preparation of titanium dioxide reflective film layer: Compared with Example 9, the only difference is that modified zinc sulfide is not added, and the other preparation steps are exactly the same, and finally a titanium dioxide reflective film layer is obtained.

[0079] Comparative Example 2

[0080] Preparation of titanium dioxide reflective film layer: Compared with Example 9, the only difference is that no hot pressing plate is used to perform hot pressing on one side of the film, and the other preparation steps are exactly the same, and finally a titanium dioxide reflective film layer is obtained.

[0081] Comparative Example 3

[0082] Preparation of titanium dioxide reflective film layer: Compared with Example 9, the only difference is that the hot pressing plate prepared in Example 5 is replaced by the following high-density convex hot pressing plate, and the other preparation steps are exactly the same, and finally a titanium dioxide reflective film layer is prepared.

[0083] The preparation steps of the high-density convex hot-pressed plate are as follows: take an austenitic stainless steel plate with a length of 10 cm, a width of 5 cm, and a thickness of 4 mm, and use a laser beam to evenly open hemispherical pits on one side of the stainless steel plate. The diameter of the pits is 15 um, the depth is 8 um, and the distance between two adjacent pits is 35 um.

[0084] Comparative Example 4

[0085] Preparation of titanium dioxide reflective film layer: Compared with Example 9, the only difference is that the hot pressing plate prepared in Example 5 is replaced by the following high-density convex hot pressing plate, and the other preparation steps are exactly the same, and finally a titanium dioxide reflective film layer is prepared.

[0086] The preparation steps of the high-density convex hot-pressed plate are as follows: take an austenitic stainless steel plate with a length of 10 cm, a width of 5 cm, and a thickness of 4 mm, and use a laser beam to evenly open hemispherical pits on one side of the stainless steel plate. The diameter of the pits is 15 um, the depth is 8 um, and the distance between two adjacent pits is 65 um.

[0087] Test example

[0088] Preparation of UV-resistant screen protector:

[0089] First, the titanium dioxide reflective film layer is cut into square sheets with a length of 5 cm and a width of 3 cm. Then, the tempered glass adhesive is evenly coated on the side of the titanium dioxide reflective film layer without convex points, and a tempered glass film layer is formed after drying. Then, the UV absorbing adhesive is evenly coated on the side of the titanium dioxide reflective film layer with convex points, and a UV absorbing film layer is formed after drying.

[0090] A pressure-sensitive adhesive layer is evenly coated on the surface of the tempered glass film layer, and then a release film layer is attached to the pressure-sensitive adhesive layer; a PET synthetic adhesive liquid is evenly coated on the UV absorbing film layer, and a PET synthetic film layer is formed after drying, thereby obtaining an anti-UV screen protective film.

[0091] The preparation method of the tempered glass adhesive is as follows: tempered glass (for laboratory use only, purchased from Taobao) is melted at high temperature to obtain the tempered glass adhesive;

[0092] UV absorbing glue was purchased from Hangzhou Tuomu Technology Co., Ltd.;

[0093] The pressure-sensitive adhesive layer uses silicone pressure-sensitive adhesive purchased from Dongguan Keli Adhesive Co., Ltd.

[0094] The release film layer uses a fluorine release film purchased from Tianjin Zhengzhong New Materials Co., Ltd.

[0095] PET synthetic glue was purchased from Shenzhen Kedas Glue Co., Ltd.

[0096] Test Example 1-8

[0097] According to the above method, the titanium dioxide reflective film layers prepared in Examples 7-11 and Comparative Examples 1-4 were used to prepare anti-UV screen protective films, respectively, to obtain 9 groups of anti-UV screen protective films. The anti-UV properties of the 9 groups of anti-UV screen protective films were tested using a lens test spectrophotometer, including UV transmittance and UV reflectivity. The test results are as follows:

[0098] Table 1

[0099] UV transmittance (100%) UV reflectivity (100%) Example 7 0.043 99.98 Example 8 0.034 99.99 Example 9 0.024 99.99 Example 10 0.030 99.99 Embodiment 11 0.045 99.99 Comparative Example 1 1.356 96.34 Comparative Example 2 1.467 97.12 Comparative Example 3 0.997 95.43 Comparative Example 4 1.213 95.52

[0100] By analyzing the data in Table 1, it can be known that the anti-UV screen protective film prepared with the titanium dioxide reflective film layer of Examples 7-11 has a significantly lower UV transmittance and a significantly higher UV reflectivity than the anti-UV screen protective film prepared with the titanium dioxide reflective film layer of Comparative Examples 1-4, which indicates that the anti-UV screen protective film of the present invention has stronger anti-UV performance.

[0101] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. An anti-UV screen protective film, characterized in that: It includes a release film layer, a pressure-sensitive adhesive layer, a tempered glass film layer, a titanium dioxide reflective film layer, a UV absorption film layer and a PET synthetic film layer stacked in sequence; wherein the titanium dioxide reflective film layer includes modified zinc sulfide, and the components of the modified zinc sulfide include zinc sulfide nanoparticles and SPN type additives in a mass ratio of 1: (0.5-0.8).

2. The anti-UV screen protection film according to claim 1, characterized in that: The preparation method of the modified zinc sulfide comprises: mixing zinc sulfide nanoparticles with an SPN type additive and then performing ultrasonic stirring to make the zinc sulfide nanoparticles and the SPN type additive fully and evenly mixed, so as to obtain the modified zinc sulfide.

3. The anti-UV screen protective film according to claim 2, characterized in that: The method for preparing the titanium dioxide reflective film layer comprises the following steps: S1: At room temperature, slowly drop titanium alkoxide into the solvent while stirring, then slowly add an appropriate amount of hydrochloric acid while stirring, adjust the pH to 1-2, and react for 2-3 hours to obtain a uniform and transparent sol solution; S2: uniformly mixing the sol solution with the modified zinc sulfide in a mass ratio of 2:(0.5-1.2) to obtain a mixed sol solution; S3: evenly coating the mixed adhesive on the cleaned substrate material, and then vacuum drying the substrate material coated with the mixed adhesive at 60-80° C. for 7-8 hours to completely evaporate the solvent to obtain a film; S4: placing the substrate material loaded with the thin film in a heating furnace for heat treatment at 400-600° C. for 2-4 hours, so that the organic matter in the thin film is completely decomposed to obtain a titanium dioxide thin film; S5: After the titanium dioxide film is taken out of the heating furnace, a hot pressing plate with pits evenly distributed on the hot pressing surface is immediately used to hot press one side of the film. After cooling to room temperature, the film is peeled off from the base material to obtain a titanium dioxide reflective film layer with bumps distributed on the surface.

4. The anti-UV screen protection film according to claim 3, characterized in that: In step S1, the mass ratio of the titanium alkoxide to the solvent is 1:(2-5).

5. The anti-UV screen protective film according to claim 3, characterized in that: In step S1, the titanium alkoxide is tetrabutyl titanate or tetraisopropoxy titanium.

6. The anti-UV screen protective film according to claim 3, characterized in that: In step S5, the shape of the pit is hemispherical, the diameter is 10-20 um, the depth is 5-10 um, and the distance between the center points of two adjacent pits is 40-60 um.

7. The anti-UV screen protection film according to claim 1, characterized in that: The release film layer is a silicone release film or a fluorine release film.

8. The anti-UV screen protection film according to claim 1, characterized in that: The pressure-sensitive adhesive layer is organic silicon pressure-sensitive adhesive or polyurethane pressure-sensitive adhesive.

9. The anti-UV screen protection film according to claim 1, characterized in that: The thickness of the release film layer is 50-80um, the thickness of the pressure-sensitive adhesive layer is 10-30um, the thickness of the tempered glass film layer is 60-100um, the thickness of the titanium dioxide reflective film layer is 20-50um, the thickness of the UV absorption film layer is 20-50um, and the thickness of the PET synthetic film layer is 30-70um.

10. A method for preparing an anti-UV screen protective film according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step 1: first, evenly apply the tempered glass glue on the side of the titanium dioxide reflective film layer without convex points, and form a tempered glass film layer after drying, and then evenly apply the UV absorbing glue on the side of the titanium dioxide reflective film layer with convex points, and form a UV absorbing film layer after drying; Step 2: Evenly coat the surface of the tempered glass film layer with a pressure-sensitive adhesive layer, and then attach a release film layer to the pressure-sensitive adhesive layer; Step 3: Evenly coat the UV absorbing film layer with PET synthetic glue to form a PET synthetic film layer after drying, thereby obtaining a UV screen protective film.